Transient Non-Ketotic Hyperglycinemia in a Newborn - Choudhury, Tarak; Kundu, Soumi; Das, G.C.; Dasgupta, Malay Kumar (Journal of Nepal Paediatric Society, 2017)
In encephalopathic infants, cerebrospinal fluid hyperglycinemia and elevated cerebrospinal fluid to plasma glycine ratio are considered pathognomonic of Non-ketotic hyperglycinemia (NKH). It is due to a defect of the glycine cleavage system and has poor prognosis. We present a case of transient NKH presented to us with hypotonia, recurrent apnea and seizure. Increased ratio of cerebrospinal fluid to plasma glycine concentrations of 0.16 was seen as a strong diagnostic indicator of Non-ketotic hyperglycinemia. J Nepal Paediatr Soc 2016;36(3):303-306